2023
DOI: 10.3390/v15010150
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Cat Hepadnavirus: Molecular Epidemiology and Phylogeny in Cats in Hong Kong

Abstract: Domestic cat hepadnavirus (DCH) is an emerging virus related to the hepatitis B virus (HBV). The pathogenic potential of DCH in cats remains to be established. The molecular prevalence of DCH varies widely in the regions investigated so far. The aim of this study was to determine the prevalence, load, and risk factors for DCH detection among cats in Hong Kong, and to generate molecular and epidemiological data on the DCH strains circulating in cats in Hong Kong. DCH DNA was detected using DCH-specific qPCR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
8
17
0
Order By: Relevance
“…Our phylogenetic analysis using the maximum likelihood method on all available complete sequences of DCH, and genomes of other members of the Orthohepadnavirus, Metahepadnavirus, Herpetohepadnavirus, and Avihepadvirus genera supports previous Generally, DCH/NPUST-006/TWN/2023 belongs to clade A1, proposed previously by other authors [12], while the rest of the Taiwan strains belong to clade A2 under genotype A. However, with the addition of more sequences particularly those from Türkiye and Taiwan strains, our phylogenetic analysis of the currently available DCH sequences, implemented by constructing a maximum likelihood tree using TIM+F+I+R2 as the best fit and chosen model according to the Bayesian information criterion, did not reveal robust branching support for a clear distinction between the proposed clades A1 and A2 (Figure 3).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Our phylogenetic analysis using the maximum likelihood method on all available complete sequences of DCH, and genomes of other members of the Orthohepadnavirus, Metahepadnavirus, Herpetohepadnavirus, and Avihepadvirus genera supports previous Generally, DCH/NPUST-006/TWN/2023 belongs to clade A1, proposed previously by other authors [12], while the rest of the Taiwan strains belong to clade A2 under genotype A. However, with the addition of more sequences particularly those from Türkiye and Taiwan strains, our phylogenetic analysis of the currently available DCH sequences, implemented by constructing a maximum likelihood tree using TIM+F+I+R2 as the best fit and chosen model according to the Bayesian information criterion, did not reveal robust branching support for a clear distinction between the proposed clades A1 and A2 (Figure 3).…”
Section: Resultssupporting
confidence: 87%
“…Phylogenetic relationships among the Taiwan strains, particularly the divergence of DCH/NPUST-006 from the other strains as observed in Figure 3, are strongly supported by the phylogenetic trees based on sequences of core, polymerase, surface, and X proteins (Figure 4). Maximum-likelihood trees of both the polymerase and surface proteins (Figures 4a and 4b) generally show the two subdivisions of Genotype A as proposed previously by other authors [12]. However, similar to that of the whole genome sequence tree, there is no robust bootstrap support for this proposed subdivision.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Our phylogenetic analysis results showed that all positive samples obtained from domestic cats from Türkiye localized into Orthohepadnavirus genus. These findings raise the question of whether DCH can affect other domestic (Capozza, Decaro et al, 2021;Capozza et al, 2023;Choi et al, 2022;Diakoudi et al, 2022) or wild carnivores. We believe that future studies investigating hepadnaviruses in different carnivorous species are needed to understand the origin of DCH and its relationship with other species.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, an HBV-like virus, domestic cat hepadnavirus (DCH), was identified in domestic cats in Australia and was associated with feline chronic hepatitis (Aghazadeh et al, 2018), suggesting a similarity with HBV pathogenesis. Subsequently, DCH was identified in other countries, including Italy (Lanave et al, 2019), Thailand (Piewbang et al, 2020), Malaysia (Anpuanandam et al, 2021), United Kingdom (Jeanes et al, 2022), United States (Stone et al, 2022), Hong Kong (Capozza et al, 2023), and Japan (Takahashi et al, 2022). DCH has a partially double-stranded, circular DNA genome of ~3,200 bases in length (Aghazadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%